NUTRACEUTICALS – AN OVERVIEW - S. MANIKANDASELVI; V. VADIVEL; P. BRINDHA (International Journal of Pharma and Bio Sciences, 2016)
The nutraceuticals have many physiological effects on the health of consumers. The upper limit of the physiological effect dimension would be food that can cure or heal certain diseases. Nutraceuticals also have the benefits beyond to its basic nutritional functions. It is important to distinguish nutritional deficiency from other physiological effects such as disease risk reduction. Nutraceuticals may range from dietary supplements to genetically engineered foods, herbal products and processed foods. This article outlines the nutraceuticals with their groups, international and national status, need, safety, merit, existing nutraceutical products, major nutraceutical companies, therapeutic applications and also stressed the urgent need for R & D in the formulation of nutraceuticals.